Impact of Contact Force Technology on Atrial Fibrillation Ablation: A Meta‐Analysis. Issue 9 (September 2015) - Shurrab, Mohammed; Di Biase, Luigi; Briceno, David F.; Kaoutskaia, Anna; Haj‐Yahia, Saleem; Newman, David; Lashevsky, Ilan; Nakagawa, Hiroshi; Crystal, Eugene
Abstract : Background: Catheter–tissue contact is essential for effective lesion formation, thus there is growing usage of contact force (CF) technology in atrial fibrillation ablation. We conducted a meta‐analysis to assess the impact of CF on clinical outcomes and procedural parameters in comparison to conventional catheter for atrial fibrillation ablation. Methods and Results: An electronic search was performed using major databases. Outcomes of interest were recurrence rate, major complications, total procedure, and fluoroscopic times. Continuous variables were reported as standardized mean difference; odds ratios were reported for dichotomous variables. Eleven studies (2 randomized controlled studies and 9 cohorts) involving 1428 adult patients were identified. CF was deployed in 552 patients. The range of CF used was between 2 to 60 gram‐force. The follow‐up period ranged between 10 and 53 weeks. In comparing CF and conventional catheter groups, the recurrence rate was lower with CF (35.1% versus 45.5%, odds ratio 0.62 [95% CI 0.45–0.86], P =0.004). Shorter procedure and fluoroscopic times were achieved with CF (procedure time: 156 versus 173 minutes, standardized mean difference −0.85 [95% CI −1.48 to −0.21], P =0.009; fluoroscopic time: 28 versus 36 minutes, standardized mean difference −0.94 [95% CI −1.66; −0.21], P =0.01). Major complication rate was lower numerically in the CF group but not statistically significant (1.3% versus 1.9%, odds ratio 0.71 [95% CI 0.29–1.73], P =0.45). Conclusions: The use of CF technology results in significant reduction of the atrial fibrillation recurrence rate after atrial fibrillation ablation in comparison to the conventional catheter group. CF technology is able to significantly reduce procedure and fluoroscopic times without compromising complication rate.